PENGARUH PASSIVE STRETCHING TERHADAP KEMAMPUAN KAYANG SENAM LANTAI MAHASISWA PENDIDIKAN JASMANI UNTAN - Serin Serin; Mimi Haetami; Novi Yanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study was to determine the effect to passive stretching exercise on bridge up ability using passive stertching exercises and conventional stretching exercises for students of the University Physical Education study program. The sample of this study amounted to 36 students (male). Data collection techniques using pretestposttest. The results shower that there was a significant effect of passive stretching exercise on bdridge up ability from the calculation of the value (sig.) 0.000 < 0.05, meaning that there wa a significant difference in the results of bridge up ability between passive stretching exercises and conventional stretching exercises. The average posttest of the experimental calss (passive stretching exercise) was 59.56 swhile the avarage posttest of the control class (conventional stretching) was 55.17 the results of the floor exercise ability of students of Phhysical Education study program at Tanjungpura University and the effect pf passive stretching is 15%.Keywords: Gymnastic Bridge, Passive Stretching, Physical Education.